Hypertenze a chronická renální insuficience--chronické selhání ledvin - Monhart, V (Vnitrni lekarstvi, 2003)
The prevalence of hypertension in patients with chronic renal insufficiency is high. In the stage of renal insufficiency it is 60% and in conservatively terminal renal failure it is as high as 90%. After the initiation of dialyzation treatment it declines temporarily, it is higher during chronic haemodialysis (50-80%) and lower in continuous ambulatory peritoneal dialysis (30%). After transplantation it is recorded in 70-80% recipients of a renal graft. Among the causes of renal hypertension in subjects with conservatively treated chronic renal insufficiency at present secondary renal impairment is increasing--in type 2 diabetes and also renal vascular affection due to atherosclerotic changes and essential arterial hypertension. Approximately 30% of patients where chronic dialyzation treatment is started, come "from the street". In the pathogenesis of renal hypertension sodium retention is involved with volume expansion and an impaired ratio of the formation of vasoactive (vasopressor and vasodepressor) substances. In chronic renal failure the volume component of hypertension predominates markedly. The causes of the development of hypertension after renal transplantation are multifactorial and are most closely associated with immunosuppressive treatment and graft rejection. Pharmacological treatment of renal hypertension prefers inhibitors of the angiotensin converting enzyme (possibly angiotensin II antagonists) because of their concurrent renoprotective action. In the stage of renal insufficiency they call for reduced doses and combination with other antihypertensive agents. The objective of treatment is to achieve a blood pressure < 130/80 mm Hg. In chronic dialyzation treatment the main therapeutic provision in hypertension is adjustment of the volume of extracellular fluid by regime provisions and effective haemoelimination treatment. Calcium blockers are useful in particular in the treatment of hypertension in haemodialyzed subjects and in hypertension after renal transplantation.
Keywords: Renal Dialysis; Kidney Failure, Chronic; Humans; chronické selhání ledvin; dialýza ledvin; Hypertension, Renal; lidé; renální hypertenze